2019
DOI: 10.24272/j.issn.2095-8137.2019.036
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of Valentin’s rock lizard (Darevskia valentini) in Armenia

Abstract: Valentin’s rock lizard ( Darevskia valentini ) is suggested to be the parent for several parthenogenetic species (e.g., D. armeniaca , D. bendimahiensis, D. sapphirina , and D. unisexualis ) that evolved through hybridization. Complex evolutionary processes (including reticulate evolution) are occurring within the areas where Valentin’s rock lizard coexists with these and other rock lizards. Hence, a detailed biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the course of our studies (Galoyan et al, 2019a(Galoyan et al, , 2019b, we have noticed that dermal structures on the dorsal part of the claw sheath are multilayered, and we have suggested that these layers could be useful for age estimation in lizards. We put forward that the proposed procedure might be an effective supplementary method accompanying the skeletochronological method, as it may allow for the use of two different structures placed on the same finger to doublecheck the esteemed age.…”
Section: Dear Editormentioning
confidence: 85%
“…In the course of our studies (Galoyan et al, 2019a(Galoyan et al, , 2019b, we have noticed that dermal structures on the dorsal part of the claw sheath are multilayered, and we have suggested that these layers could be useful for age estimation in lizards. We put forward that the proposed procedure might be an effective supplementary method accompanying the skeletochronological method, as it may allow for the use of two different structures placed on the same finger to doublecheck the esteemed age.…”
Section: Dear Editormentioning
confidence: 85%
“…The reason for this is not clear. It may be competition for food: rock lizards eat arthropods of appropriate size (Darevsky 1967;Tsellarius and Tsellarius 2001;Galoyan et al 2019). Like other ectothermic organisms feeding on small invertebrates (e.g., Kuzmin and Tarkhnishvili 1992), they hardly can seriously affect the abundance of insects; rather, a high concentration of animals may decrease the hunting success.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on longitudinal monitoring, ecological and behavioural studies suggest that toe-clipping and distal nger phalanx analysis should be used to collect the material [11][12][13][14][15]. These methods allow the researchers to conduct a life-long study to estimate the growth pattern of individuals.…”
Section: Introductionmentioning
confidence: 99%